Optimalisasi Output Photovoltaic Menggunakan Pendingin Air Pada Pembangkit Listrik Tenaga Surya Terapung - Supriyono; Yusuf, Muhamad; Purwiyanto (P3M Politeknik Negeri Cilacap, 2024)
Land requirements are one of the obstacles to developing solar power plants . One solution is to utilize the surface of the reservoir for the construction of floating solar power plants. Excessive heat from sunlight received by photovolataics reduces the effectiveness of floating solar power plants output. Excessive heat in photovoltaics can be reduced by cooling methods. In this research, a photovoltaic cooling system using water was developed. A water pump is installed to channel reservoir water to the photovoltaic surface. The cooling system uses two methods, namely the sensor and timer method. In the sensor method, a sensor is installed on the solar power plants to detect the photovoltaic surface temperature. If the temperature detected by the sensor exceeds the photovoltaic effectiveness limit, the water pump is started. In the timer method, the pump is run based on a preset time. Based on the test results, the cooling system is able to increase the photovoltaic voltage output. The average value of the timer mode cooled photovoltaic voltage is 3.79% higher compared to the photovoltaic voltage without cooling and the average value of the sensor mode cooled photovoltaic voltage is 1.02% higher than the photovoltaic voltage without cooling.